More efficient utilization of fish and fisheries products : proceedings of the international symposium on the occasion of the 70th anniversary of the Japanese Society of Fisheries Science, held in Kyoto, Japan, 7-10 October 2001 - Sakaguchi, Morihiko, 1938- (Developments in food science, 2004)
Researchers in academia and industry involved in Natural Product Chemistry and Medicinal Chemistry.